Settling the Frontier : Land, Law and Society in the Peshawar Valley, 1500-1900 - Nichols, Robert (Karachi Oxford University Press, 2001)
This political and social history explores four centuries in the history of the Peshawar region, from 1500 to 1900. It examines how different residents experienced imperial expansion (from the Mughals to the British), technological innovation, and the growth of state institutions, while they simultaneously nurtured and transformed indigenous power relations, socio-cultural practices, and a political economy never completely distanced from an earlier pastoral-nomadic heritage.
Include Appendices, Maps, Glossary, Bibliography and Index.
The text examines how the region's residents experienced imperial expansion, technological innovation and the growth of state institutions, yet maintained indigenous power relations and socio-cultural practices.
Keywords: Pushtuns -- Pakistan--Peshawar Region -- Pakistan--Peshawar -- Politics and government